The structure of precursor mRNAs and of excised intron RNAs in chloroplasts of Euglena gracilis - Koller, Barbara (1985)
Partially spliced precursor mRNAs (pre-mRNAs) in the steady-state population of RNA from chloroplasts of Euglena gracilis were found by electron microscopy. The structure and the frequency of the pre-mRNAs of the psbA gene (the gene for the 32-kd protein of photosystem II), which is split by four introns in Euglena chloroplasts was analysed by electron microscopy. A chloroplast DNA (cpDNA) fragment containing the psbA gene from Euglena, was cloned into a pEMBL vector. The single-stranded recombinant phage DNA of the coding strand was prepared and hybridized with cpRNA. The majority of hybrids were formed with mature mRNA, but ˜8% of the hybrids were formed with pre-mRNAs. The pre-mRNAs were either unspliced or incompletely spliced. A detailed analysis of the structure and the frequency of the pre-mRNAs of the psbA gene showed that the four introns are neither spliced out in a strictly random way, nor in a 5'-3' or 3'-5' direction. Introns 2 and 3 are preferentially spliced out first, intron 1 intermediately and intron 4 is generally spliced out last. However, this sequence is not a strict rule. We conclude that the introns can be spliced independently, each one at a different rate. The coding strand from a fragment of the psbA gene was separated and annealed with low mol. wt. cpRNA, which was isolated from an agarose gel. Small circular hybrids were found at the positions of the four introns, demonstrating for the first time covalently closed circular excised intron RNAs (iRNAs) in chloroplasts.